Female non-smokers’ environmental tobacco smoking exposure by public transportation mode - Kim, Seyoung (Ann Occup Environ Med, 2018)
BACKGROUND: This study aimed to analyze environmental tobacco smoking exposure in female nonsmokers by public transportation mode using representative data of Koreans. METHODS: Data from the Second Korean National Environmental Health Survey (2012–2014) were analyzed. Urine cotinine was analyzed by public transport behavior, secondhand smoke exposure, socioeconomic factors, and health-related factors. Participants were 1322 adult females; those with the top 75% urine cotinine concentrations were assigned to the high exposure group. A logistic regression analysis was performed considering appropriate weights and stratification according to the sample design of the Second Korean National Environmental Health Survey. RESULTS: The geometric mean of urine cotinine concentrations differed according to public transportation modes: subway (1.66 μg/g creatinine) bus (1.77 μg/g creatinine), and taxi (1.94 μg/g creatinine). The odds ratio [OR] was calculated for the high exposure group. The OR of the taxi (2.39; 95% confidence interval, 1.00–5.69) was statistically significantly higher than the subway value (reference), and marginally significant after adjusted with life style, sociodemographic factors and involuntary smoking frequency (2.42, 95% confidence interval, 0.97–6.04). CONCLUSIONS: The odds ratio of passengers who mainly used taxis was marginally significantly higher than those of passengers who used subways and buses after adjusted with life style and sociodemographic factors. Implementation of supplementary measures and further studies on exposure to environmental tobacco smoking in taxis are warranted.